The Effect of Hyperbaric Oxygen Therapy on Reducing Blood Cortisol Levels in Individuals with Anxiety Disorders - Hisnindarsyah, Hisnindarsyah; Nandaka, I Ketut Tirka (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research pertains to developmental advancements in the health and maritime sectors, specifically focusing on diving and hyperbaric oxygen therapy's (HBO) application. The study holds the potential to enhance comprehension regarding the Effects of Hyperbaric Oxygen Therapy (HBO) in addressing anxiety disorders, thus contributing significantly to the realms of health and maritime industries. Hyperbaric oxygen therapy involves subjecting patients to heightened pressure environments while administering pure oxygen at levels exceeding atmospheric pressure, with a minimum clinical threshold of 1.4 ATA. (HBO) interventions, utilized for countering hypoxia and cortisol reduction, exhibit promise in mitigating anxiety disorders. The research methodology commences with a systematic screening procedure employing an anxiety disorders questionnaire, ensuring the acquisition of a well-defined, credible, consistent, and unbiased participant pool. Employing a quasi-experimental design featuring a randomized pre-post control group arrangement, the study targets males aged 25-40 with anxiety disorders, drawn from Dr. Ramelan Surabaya's psychiatric clinic.